Growth kinetics of IMC at the solid Cu/liquid Sn interface. Issue 3 (14th February 2018) - Yin, Zuozhu; Sun, Fenglian; Liu, Yang; Liu, Yang
Abstract : Purpose: The purpose of this paper is to investigate growth kinetics of interfacial Cu-Sn intermetallic compound (IMC) at the solid Cu/liquid Sn interface. Design/methodology/approach: The Sn/Cu solid–liquid interfacial IMCs are fabricated under various soldering temperatures (240°C-270°C) and soldering times (5-240 s) by dipping method. The thickness and morphology of IMC are observed and analyzed by the optical microscope and scanning electron microscope. Findings: Holding at 260°C, Cu/Sn solid–liquid interface Cu6 Sn5 growth index experience a change from 0.08 to 0.30 within 10-190 s. The growth index is 0.08 in 10-40 s; the growth index is 0.30 in 40-190 s. Cu6 Sn5 grain coarsening index is constant within 10-190 s. It is 0.13. The result of the index of Cu6 Sn5 grain coarsening is different from predecessors 27 results Cu6 Sn5 grain coarsening index for 1/3. This is because Cu6 Sn5 grain grows at the expense of its near small grain to reduce the surface Gibbs free energy, and its morphology changes from regular shape to irregular shape. It sets up the mathematical expression about the initial formation time and temperature of Cu3 Sn in 240°C-270°C. Originality/value: It obtains a mathematical model to express the changes of solid–liquid interface frontier concentration which has an effect on the interfacial Cu6 Sn5 layer growth index and the Cu6 Sn5 grain coarsening index. Different indexes can be obtained by establishing relevance equations, which can be used to predict the growth of the interface IMC layer. This mathematical model is established to design the solder pads and the sizes of the solder joints.